Pengaruh Laverage, Risiko Kredit dan Intellectual Capital terhadap Kinerja Keuangan Perbankan - Ajeng Marsela Setiawan; Oktavima Wisdaningrum; Bambang Wicaksono (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2026)
This study aims to examine and analyze the influence of leverage, credit risk, and intellectual capital on banking financial performance. This quantitative study uses secondary data in the form of financial statements listed on the Indonesia Stock Exchange (IDX) for the period 2019-2024. The sample used in this study was 72 observational data using a purposive sampling method. Data analysis used descriptive statistics, classical assumption tests, multiple linear regression, hypothesis testing, and coefficient of determination tests. The results show that leverage has a negative effect, credit risk has no effect, and intellectual capital has a positive effect on financial performance.